A facile template method to fabricate one-dimensional Fe3O4@SiO2@C/Ni microtubes with efficient catalytic and adsorption performance. Issue 42 (15th October 2021) - Yang, Liting; Zheng, Jing; Xu, Jingli; Zhang, Baishun; Zhang, Min
Abstract : The Fe3 O4 @SiO2 @C/Ni microtubes were well constructed with MoO3 microrods as sacrificing template, which manifested excellent performance as both catalyst and adsorbent. Abstract : Herein, we report a facile approach for preparing Fe3 O4 @SiO2 @C/Ni microtubes, which could be used as both a catalyst and adsorbent. During the synthetic process, two coating layers (SiO2 and PDA-Ni 2+ layers) are polymerized on the surface of MoO3 @FeOOH in turn with an extended Stöber method using MoO3 microrods as sacrificing templates. Notably, the coating of inorganic SiO2 and organic PDA-Ni 2+ layers and the removal of MoO3 cores are easily achieved simultaneously in ammonia solution with a one-step reaction. Interestingly, the coated silica not only protects the Fe3 O4 nanoparticles, but also suppresses the reverse electron transfer from PDA to Fe3 O4 in a calcination process, which leads to the in situ reduction of Ni 2+ that enhances the dispersibility and density of the Ni nanoparticles. The resulting Fe3 O4 @SiO2 @C/Ni hybrid microtubes can be used as a catalyst towards the reduction of 4-nitrophenol (4-NP) in the presence of NaBH4 . Meanwhile, they also exhibit highly selective adsorption on His-rich proteins (BHb). Moreover, the hybrid microtubes can be conveniently separated with an extra magnetic field due to the presence of Ni and Fe3 O4, and they show good cyclic stability, which is important for practical applications.